Validación del Inventario Situacional de Consumo de Alcohol en personas que buscan tratamiento en México - Emmanuel Said Baeza Torres; Leticia Echeverría San Vicente; Eduardo Velasco-Rojano; Sara Eugenia Cruz Morales (Centros de Integración Juvenil A.C., 2018)
Introduction: before starting treatment, it is necessary to know the pattern of consumption, to determine the background, risk situations that lead the individual to harmful drinking, among other variables. So far there is no validated instrument, in Mexico to measure the situations that precipitate the consumption of alcohol in alcoholic population. Objective: validate the Situational Inventory of Alcohol Consumption (ISCA) in the Mexican population consuming alcohol. Method: a sample of 592 (88.2% men, 11.8% women), whose ages ranged between 18 and 30 years of age (M = 21.13, SD = 2.26) was gotten, who requested psychological attention for problems with their alcohol consumption, of which 66.2% reported low dependency and 33.8% moderate dependence. Results: a robust maximum likelihood confirmatory analysis was performed, with which a reliable (α = .96) and valid instrument was obtained, with an explained variance of 59%. Discussion and conclusion: a valid, reliable and brief instrument applicable in brief interventions for users who seek treatment for alcohol consumption. ---- Introducción: antes de empezar el tratamiento, es necesario conocer el patrón de consumo, determinar los antecedentes y las situaciones de riesgo que llevan al individuo a consumir en exceso, entre otras variables. Hasta el momento no se cuenta con un instrumento validado en México que mida las situaciones que precipitan el consumo de alcohol. Objetivo: validar el Inventario situacional de consumo de alcohol (ISCA) en población mexicana consumidora de esta sustancia. Método: se obtuvo una muestra de 592 (88.2% hombres, 11.8% mujeres), cuyas edades oscilaron entre los 18 y los 30 años de edad (M = 21.13, S.D. = 2.26), que solicitaron atención psicológica por problemas con su consumo de alcohol, de los cuales 66.2% reportó dependencia baja y 33.8%, dependencia moderada. Resultados: se realizó un análisis confirmatorio de máxima verosimilitud robusta, con el que se obtuvo un instrumento confiable (α = .96) y válido, con una varianza explicada del 59%. Discusión y conclusión: se obtuvo un instrumento válido, confiable y breve aplicable en intervenciones breves para usuarios que buscan tratamiento para consumo de alcohol.